Redes de inovação: mapeamento de inventores de patentes em uma empresa do setor de cosméticos - Serrano, Bruno (2014)
This article aims to identify patterns in the organization of innovation network by mapping the network inventors of a cosmetics company and identifying ways to promote innovation capacity through interconnectivity. The research was conducted through case study methods, and, for this, inventors mappings were made, based on the records of patents previously surveyed, taking into consideration the linkage (internal or external) of each inventor with the company and also the amount of patent citations. It was identified higher hierarchy in networks with the presence of collaborators externals to the company as well as a possible higher technological content, since the amount of citations was higher compared to other networks. It is verified, finally, that inventors mappings (although a patent is not the only measuring factor of innovation) can identify key features to help a better management of innovation.